Measurement of turbulent flame speed of natural gas/air mixtures at elevated pressure - Li, L.; Witton, John J. (Cranfield University, 2010)
Turbulent flame speeds were measured over a range of pressures to 0.8 MPa using a jet flow apparatus fired with a synthetic mixture representing a mid-European natural gas. The equivalence ratio empty set was 0.9. The gas contained significant proportions of ballast gases and higher hydrocarbons. The method adopted was the 'flame angle' technique, using schlieren imaging to obtain the flame vertex angle from the peak density gradient. Image analysis techniques were developed to reduce interpretation errors and give an unbiased result. The data show higher flame speeds than those obtained with pure methane at elevated pressures, using similar methodology, and has an application in numerical modelling of combustors.
Keywords: Combustion; Fuels; Flame speed; Numerical modelling